Penerapan Model Pembelajaran Berbasis Masalah Untuk Meningkatkan Hasil Belajar Peserta Didik Pada Konsep Gaya Di Kelas VII SMP Negeri 35 Halmahera Selatan - Irawati H. Malan (Peneliti.net, 2022)
This study aims to improve the learning outcomes of seventh grade students of SMP Negeri 35 South Halmahera through the application of a problem-based learning model. Which is carried out in 2 cycles. The research subjects were students of class VII SMP Negeri 35 South Halmahera, totaling 30 students. Sources of data came from teachers and students. The technique of collecting research data was carried out using observation sheets on the implementation of the learning model and test questions. The data analysis used is descriptive analysis by calculating individual learning mastery and classical learning completeness. The results of the quantitative analysis based on the Science and Physics learning outcomes test, the average score for pre-action was 40 and there was an increase in learning outcomes to an average of 56.39 in the first cycle, then there was also an increase in learning outcomes of 75.94 in the second cycle, these results show an increase in student learning outcomes during the physics science learning process through the application of a problem-based learning model (PBL). The conclusion of this study is the application of a problem-based learning model to improve student learning outcomes on the concept of style in class VII SMP Negeri 35 South Halmahera.